Employing reflective practice to capture Indonesian EFL pre-service teachers' conceptions of English learning - Harahap, Hilyati Fitria; Fithriani, Rahmah (Journal on English as a Foreign Language, 2024)
Understanding the English language learning concept is crucial for success in learning English. Numerous studies have focused on English as a foreign language (EFL) in-service teachers' perceptions of English language learning, while only a few have examined EFL pre-service teachers. This research delves into the different aspects of the experiences, reflections, and conceptualizations of English language learning among EFL pre-service teachers. A group of eight Indonesian EFL pre-service teachers engaged in participatory action research (PAR) during their field experience practices (PPL) in junior and senior high schools. This study employed a thorough approach to data collection, incorporating photovoice, an open-ended questionnaire, and in-depth interviews. The results of data analysis involving identifying and categorizing themes reveal a diverse range of perspectives, wherein English is likened to a lamp, dictionary, cuisine, flowers, class, and artificial intelligence (AI). Furthermore, learning English is often portrayed as an engaging and demanding process, highlighting the importance of innovative pedagogical approaches. This study emphasizes the significance of collaboration between language and technology departments to remain at the forefront of educational advancement, establishing a solid foundation for future research and improvements in EFL teacher education.